PEMBELAJARAN AKHLAQ LIL BANIN DALAM PEMBINAAN AKHLAK MULIA SISWA: DI MADRASAH TSANAWIYAH AN-NUR TANGKIT MUARO JAMBI - Yudo Handoko; Agus Lestari (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2023)
The purpose of this research was to find out the process of developing morals in learning akhlaq lil banin at MTs An-Nur Tangkit Muaro Jambi, the factors that influence students' moral development in learning akhlaq lil banin at MTs An-Nur Tangkit Muaro Jambi, to find out the obstacles in the process fostering student morals in learning akhlaq lil banin at MTs An-Nur Tangkit. This research used a qualitative approach from the perspective of the moral akhlaq lil banin teacher’s in educating students of MTs An-Nur Tangkit. The results of this research indicate the process of learning the book of akhlaq lil banin in fostering noble character at MTs An-Nur Tangkit through a) transinternalization and b) habituation in the dormitory. The material in learning akhlaq lil banin that is taught in schools can be directly practiced and accustomed to in everyday life in the dormitory under the supervision of caregivers and administrators. There are 3 factors that influence the learning of akhlaq lil banin fostering noble character, namely a) intelligence factors, b) factors environment and c) disciplinary factors. While the obstacles to learning akhlaq lil banin in fostering students' noble character at MTs An-Nur Tangkit are internal obstacles and external obstacles.